2008
DOI: 10.1016/s1875-4597(09)60004-7
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Granisetron in Preventing Postanesthetic Shivering

Abstract: The prophylactic use of granisetron 40 microg/kg is as effective as meperidine (0.4 mg/kg) and tramadol (0.1 mg/kg) in preventing postanesthetic shivering without prolonging the emergence time from anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
28
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 12 publications
3
28
2
Order By: Relevance
“…Although they used four different drugs in patients undergoing general anesthesia, they also found that granisetron was an effective drug as pethidine in preventing postanesthetic shivering compared to our study. [12] Recent studies showed that serotonin receptor antagonists (ondansetron, granisetron) are highly effective for nausea, retching, and vomiting during regional anesthesia for cesarean delivery in parturients and correlated with our results. [13] The distinctive feature of this study is that we assessed the effectiveness of one drug for prevention of both shivering, nausea and vomiting at the same time during neuroaxial block.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Although they used four different drugs in patients undergoing general anesthesia, they also found that granisetron was an effective drug as pethidine in preventing postanesthetic shivering compared to our study. [12] Recent studies showed that serotonin receptor antagonists (ondansetron, granisetron) are highly effective for nausea, retching, and vomiting during regional anesthesia for cesarean delivery in parturients and correlated with our results. [13] The distinctive feature of this study is that we assessed the effectiveness of one drug for prevention of both shivering, nausea and vomiting at the same time during neuroaxial block.…”
Section: Discussionsupporting
confidence: 87%
“…The mechanism for 5-HT3receptor antagonists is still unclear but is thought to be related to inhibition of serotonin reuptake on the preoptic anterior hypothalamic region. [7,[10][11][12][13] In a study by Kim et al on 52 patients who had undergone knee arthroscopy under spinal anesthesia, romasetron, a selective serotonin 5-HT3 receptor antagonist effectively prevent shivering during spinal anesthesia that was correlated with our study. [10] In a study by Sagir et al on 160 patients undergoing urological surgery under spinal anesthesia with bupivacaine, the patients were randomly allocated to receive saline (Group P, n = 40), ketamine 0.5 mg (Group K, n = 40), granisetron 3 mg (Group G, n = 40) or ketamine 0.25 mg + granisetron 1.5 mg (Group KG, n = 40).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In various studies, some other 5-HT antagonists such as tramadol were used for prevention or treatment of shivering and in most of them, reduction in sweating, vasoconstriction, and shivering threshold were reported (9, 13, 14). Granisetron, which is also a new 5-HT3 inhibitor and is mostly used to control of postoperative nausea and vomiting, is recently used for prevention of POS (15, 16). These studies indicate the role of serotonin receptors in thermoregulation at different levels.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is also reported that central α 2 -receptor activation inhibits norepinephrine-induced firing activity on the dorsal raphe nucleus and decreases central thermo-sensitivity (20), and that the suppressive effects of Dexmedetomidine on serotonergic activity in the locus ceruleus, nucleus tractus solitarii, and raphe dorsalis contribute to its anti-shivering effect (21,22).…”
Section: Discussionmentioning
confidence: 99%